Network architecture of verticality processing in the human thalamus - Conrad, Julian; Baier, Bernhard; Eberle, Laurenz; Ruehl, Ria Maxine; Boegle, Rainer; Zwergal, Andreas; Dieterich, Marianne (Annals of neurology, 2023)
Objective Thalamic dysfunction in lesions or neurodegeneration may alter verticality perception and lead to postural imbalance and falls. The aim of the current study was to delineate the structural and functional connectivity network architecture of the vestibular representations in the thalamus by multimodal magnetic resonance imaging. Methods Seventy-four patients with acute unilateral isolated thalamic infarcts were studied prospectively with emphasis on the perception of verticality (tilts of the subjective visual vertical [SVV]). We used multivariate lesion-symptom mapping based on support-vector regression to determine the thalamic nuclei associated with ipsiversive and contraversive tilts of the SVV. The lesion maps were used to evaluate the white matter disconnection and whole brain functional connectivity in healthy subjects. Results Contraversive SVV tilts were associated with lesions of the ventral posterior lateral/medial, ventral lateral, medial pulvinar, and medial central/parafascicular nuclei. Clusters associated with ipsiversive tilts were located inferiorly (ventral posterior inferior nucleus) and laterally (ventral lateral, ventral posterior lateral, and reticular nucleus) to these areas. Distinct ascending vestibular brainstem pathways terminated in the subnuclei for ipsi- or contraversive verticality processing. The functional connectivity analysis showed specific patterns of cortical connections with the somatomotor network for lesions with contraversive tilts, and with the core multisensory vestibular representations (areas Ri, OP2-3, Ig, 3av, 2v) for lesions with ipsiversive tilts. Interpretation The functional specialization may allow both a stable representation of verticality for sensorimotor integration and flexible adaption to sudden changes in the environment. A targeted modulation of this circuitry could be a novel therapeutic strategy for higher level balance disorders of thalamocortical origin. ANN NEUROL 2023;94:133-145
Online veröffentlicht: 26. März 2023
Gesehen am 01.07.2024